Freedom on Whose Terms? A Decolonial Re-Examination of Religion in Indonesia - Kurnia; Andi Miftahul Maulidil Mursyid (Journal of Religion and Decoloniality, 2025)
Restrictions on freedom of religion in Indonesia lead to discrimination against religious groups and generate social pressures reinforcing practices of intolerance. This situation highlights the urgency of rethinking the decolonial process in the legal framework of religious freedom, particularly regarding the recognition of the rights of indigenous belief systems (aliran kepercayaan) and religious minorities. This study employs a qualitative approach grounded in decolonial theory, drawing on data from Setara Institute reports spanning from 2014 to 2024. It addresses three central questions: How can decoloniality be interpreted within the context of religion in Indonesia; How does religious freedom challenge contemporary manifestations of colonialism, and; How do colonial legacies continue to shape current religious expressions and legal structures? First, colonial-era thought structures still influence the persistence of religious intolerance in Indonesia; Second, the existing legal framework continues to reproduce exclusive interpretations of religious freedom, contributing to the ongoing marginalization of minority groups, and; Third, dominant political-legal frameworks perpetuate conditions that lead to the violation of religious freedom. These findings suggest that freedom of religion in Indonesia has terms and conditions that must be critically examined.